2019
DOI: 10.18632/aging.102301
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognosis significance of cardiovascular disease in cancer patients: a population-based study

Abstract: Background: Cardiovascular disease (CVD) is a heavy burden on cancer patients worldwide. This study aimed to evaluate the prevalence and influence of cardiovascular risk factors (CVRF) and CVD on the all-cause mortality among Chinese cancer patients.Results: Overall, 13.0% of all cancer patients had at least one type of CVRFs and 5.0% with CVDs. Patients with CVRF or CVD presented more frequently at later stages and received higher percentage of oncotherapy. During 1,782,527 person-years of follow-up, the all-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
2
25
2
1
Order By: Relevance
“…Besides the abovementioned death reasons, pneumonia and influenza, hypertension as well as atherosclerosis have in the present study been found to be significantly more frequent in older CRC patients in comparison to not only the overall US population but also to the younger aged CRC patient groups. Dong Liu et al reported on the continuous increase of, especially, cardiovascular disease but also hypertension, heart failure, and atrial fibrillation in cancer patients with old age 20 . This adds to the fact that aging itself is a risk factor for cancer development 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the abovementioned death reasons, pneumonia and influenza, hypertension as well as atherosclerosis have in the present study been found to be significantly more frequent in older CRC patients in comparison to not only the overall US population but also to the younger aged CRC patient groups. Dong Liu et al reported on the continuous increase of, especially, cardiovascular disease but also hypertension, heart failure, and atrial fibrillation in cancer patients with old age 20 . This adds to the fact that aging itself is a risk factor for cancer development 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a competing risk model is generally considered more appropriate when patients have other competing risks of death. This is particularly true for patients with lung cancer who are likely to be older and may be afflicted with other pulmonary or cardiac conditions that can represent a serious threat to their overall health [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have primarily focused on the long-term cardiovascular complications of cancer treatments [ 17 , 18 ]. Data related to the prevalence of pre-existing cardiovascular diseases in patients diagnosed with cancer has been reported to range from 5 to 43%, depending on the primary site of malignancy and the geographical region where the study was conducted [ 19 , 20 ]. However, there are limited studies reporting on the impact of pre-existing cardiovascular disease on subsequent treatment patterns and survival outcomes of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This is largely due to the following reasons: i) Cancer and CVDs involve many common risks and pathologic factors, like smoking, diabetes, and aging (1-3); ii) Various cancer treatments cause direct or indirect damage to the cardiovascular system. According to previous investigations, over 60% of patients were prescribed cardiovascular risk drugs during cancer treatments (4,5). Conventional chemotherapy and targeted therapies are associated with an increased risk of cardiac damage including heart failure (HF), hypertension, arrhythmia, thromboembolism, and ischemic cardiomyopathy (CM), and may be life-threatening in some instances.…”
Section: Introductionmentioning
confidence: 99%